Postpartum mania in a man with bipolar disorder: case report and a review of the role of sleep loss. (25th November 2013) - Stevens, Anja WMM; Geerling, Bart; Kupka, Ralph W
<x xml:space="preserve">Abstract</x> Background In contrast to postpartum mood episodes in women with bipolar disorder, little is known about the risk of recurrence in men with bipolar disorder who have just become fathers. Case report We present the case of a man with bipolar disorder who had a manic episode immediately after becoming a father. His spouse had a normal pregnancy, and delivery started during daytime and lasted until the early morning hours. The patient subsequently developed a manic episode, which had a major impact on the family. Conclusions There is a well‐known relationship between sleep loss and the occurrence of a manic episode. The study of psychopathology in the postpartum period in relation to sleep disturbance refers mainly to women. Disturbance of sleep patterns in the perinatal and postpartum period may also negatively impact the course of bipolar disorder in the father. In cases of pregnancy of a male bipolar disorder patient's spouse, preventive strategies for the postpartum period should be planned in advance.